Effects of Essential Fatty Acid Supplementation on in vitro Fermentation Indices, Greenhouse Gas, Microbes, and Fatty Acid Profiles in the Rumen - Amanullah, Sardar Muhammad; Kim, Dong Hyeon; Paradhipta, Dimas Hand Vidya; Lee, Hyuk Jun; Joo, Young Hoo; Lee, Seong Shin; Kim, Eun Tae; Kim, Sam Churl (Frontiers in Microbiology, 2021)
This study estimated the effect of essential fatty acid (FA) supplementation on fermentation indices, greenhouse gases, microbes, and FA profiles in the rumen. The treatments used pure FAs consisting of C18:2n-6 FA (LA), C18:3n-3 FA (LNA) or a mixture of these FAs at 1:1 ratio (Combo). In vitro rumen incubation was performed in 50 mL glass serum bottles containing 2 mg of pure FAs, 15 mL of rumen buffer (rumen fluid + anaerobe culture medium = 1:2), and 150 mg of synthetic diet (411 g cellulose, 411 g starch, and 178 g casein/kg dry matter) at 39°C for 8 h with 5 replications and 3 blanks. In rumen fermentation indices, LA exhibited highest (P < 0.05) ammonia-N and total gas volume after 8 h of incubation. Furthermore, LA presented lower (P < 0.05) pH with higher (P < 0.05) total volatile fatty acid (P = 0.034) than Combo, while LNA was not different compared to those in the other treatments. Additionally, Combo produced highest (P < 0.05) CO2 with lowest (P < 0.05) CH4. In the early hour of incubation, LA improved (P < 0.005) Fibrobacter succinogen and Ruminococcus flavefaciens, while LNA improved (P < 0.005) Ruminococcus albus. After 8 h of incubation, LNA had lower (P < 0.05) methanogenic archaea than LA and Combo, but had higher (P < 0.05) rumen ciliates than LA. R. albus was higher (P < 0.05) in LA than in LNA and Combo. It was observed that the rate of biohydrogenation of n-6 and n-3 FAs was comparatively lowest (P < 0.05) in Combo, characterized by higher C18:2n-6 and/or C18:3n-3 FA and polyunsaturated FA concentrations with lower (P < 0.05) concentrations of C18:0 and saturated FA and the ratio of saturated FAs to polyunsaturated FAs. Therefore, this study concluded that dietary C18:2n-6 could improve populations of fibrolytic bacteria and rumen fermentation indices, but dietary mixture of pure C18:2n-6 and C18:3n-3 is recommended because effective to reduce enteric methane emissions and resist biohydrogenation in the rumen with less effect on rumen microbes.